Um estudo sobre o desenvolvimento linguístico de surdos autistas: estratégias, intervenções e desafios - Pereira, Helen Maia (Universidade Federal do Tocantins, 2024)
This research has as its main theme a study of the linguistic development of deaf individuals with autism. Conducting a review of the literary works developed in the field of deafness, autism, and linguistic development highlights the scarcity that still exists for the educational development of deaf individuals with autism. The central goal of work is to analysis the strategic, approaches, present methodology and contribute to appropriate interventions practices to ensure educational performance for individuals who are both deaf and autistic. The same traverses critical points in both realities, both for the deaf and the autistic, exposing their limitations according to each specificity, exemplifying both inverse conditions. The most important sources for the work were (SANTANA; 2015, FRANÇA AND PINHO; 2021, VYGOTSKY; 2007, CANÔNICO; 2020, QUADROS; 1997). The date collection was conducted brought a review of relevant literature, focusing on the analysis of 5 articles and 5 books to inform the construction of this study. Finally, we conclude that there is a lack of fully disclosed interventions. That there are no effectively proven data regarding the linguistic development of deaf individuals with autism, but there is evidence demonstrating behavioral improvement in these individuals following the applied strategies. It is important to emphasize the lack of public policies that facilitate the educational rights of these individuals. It is important to emphasize the lack of public policies that facilitate the educational rights of these individuals.